RELIGIOUS LITERACY AND CULTURAL MATERIALISM IN ELT TEXTBOOK MY NEXT WORDS: A CRITICAL DISCOURSE ANALYSIS IN THE LIGHT OF PROFIL PELAJAR PANCASILA - Sofiana, Nina; Bahri, Seful; Yulianto, Henrikus Joko (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2025)
This study investigates how religious literacy and cultural materialism are represented in My Next Words, a government-issued English textbook series for elementary schools in Indonesia, and examines their alignment with the values of Profil Pelajar Pancasila. As English language learning is expected to promote not only communicative competence but also character education, this research explores the ideological content embedded in the textbook series for Grades 1, 2, 4, and 5. Using Critical Discourse Analysis as the methodological framework, the study analyzes how texts and illustrations convey messages related to religious values, material culture, and national character dimensions. The findings reveal that while the textbooks implicitly promote politeness and individual responsibility, they lack substantive religious or cultural representation. Cultural materialism is present through the portrayal of modern, middle-class lifestyles and material possessions. Although the textbooks support aspects of independence and moral behavior, they fall short in promoting diversity, collaboration, and critical thinking. This research highlights the need for more inclusive and reflective English learning materials that align with Indonesia’s educational goals and diverse cultural realities.